Voice-enabled internet radio Android application - Chew, Ser Hiong (2014)
Smartphones had become such an essential item of our modern society that almost everyone in the world owns a smartphone. One of the reason smartphones had become so popular was due to the mobile applications that can be used in the smartphones. Applications were constantly being developed by developers and placed in the App Store or Google Play Store. A look at Google Play store revealed that the marketplace had countless of mobile applications. Despite this, there were hardly any application that was designed for the needs of the visually handicapped.